PERAN PROFITABILITAS DALAM MEMEDIASI PENGARUH DANA PIHAK KETIGA DAN PERKEMBANGAN KREDIT BANK UMUM DI BURSA EFEK INDONESIA - Pristin Prima Sari; Sri Hermuningsih; Anisya Dewi Rahmawati (MANAJEMEN DEWANTARA, 2020)
The research aims to empirically examine the effect of profitability mediation on Third Party Funds and Commercial Bank Credit on the Indonesia Stock Exchange in 2015-2018. The data analysis method is purposive sampling using Smartpls 3.0 statistical tools. The results of the study are that profitability can mediate the influence of third party funds on bank lending is significantly positive. Growth in third party funds was also followed by credit growth. The benefits of research are that bank management can be a benchmark in improving commercial bank credit performance by maximizing third party funds growth and profitability.Keywords : Third Party Funds, ROA, Credit, IDXÂ